A Bibliometric Analysis of Datafication in Education: Trends, Impact and Future Implications - Nining Anggeraini (Universitas Bumigora, 2025)
The massive use of digital learning platforms and AI in education has generated large quantities of dataon teacher and student information, online interactions, and teaching and learning practices. This data can be collected, analyzed, and interpreted to improve educational outcomes. Following the interest and attention in this topic, numerous research studies have been conducted to gain a better understanding in this area. Thus, the purpose of this study is to summarize the literature on datafication in education from 2020 to 2024 and to explore the key terms related to its influence on educational practices, and its potential future implications. The method used in this study is a bibliometric analysis. A total of 200 articles were found in Google Scholar through a search using the keywords